Peningkatan nilai parameter status besi Reticulocyte Hemoglobin Equivalent setelah pemberian suplemen besi intravena pada pasien hemodialisis reguler - Naomi Niari Dalimunthe; Abdurrahim Rasyid Lubis (Majalah Kedokteran Nusantara The Journal Of Medical School, 2014)
Introduction : Reticulocyte Hemoglobin Equivalent (RET He) is a new parameter for evaluating iron status. RET He is not influenced by chronic inflammatory conditions thus could provide better information of iron status in patients with chronic kidney disease (CKD) with regular hemodialysis. The aim of this study was to investigate the changes in RET He after iron supplementation to determine the usefulness of this marker as iron status parameter in CKD patients with regular hemodialysis.Methods : Uncontrolled clinical study was conducted at Hemodialysis Center in Adam Malik Hospital Medan during April-May 2011. A total of 15 regular hemodialysis patients with iron deficiency anemia received intravenous iron supplementation (100mg Fe sucrose) every hemodialysis session (2x/weeks) for 4 weeks. The changes in hemoglobin, hematocrit and RET He before and after the intervention were analyzed using paired t test.Results : Mean hemoglobin, hematocrit and RET He before intervention were 8.6 (SD 1.09) g/dl, 28.0 (SD 4.25)% and 29.9 (SD 3.85) pg, respectively. After intervention they were 9.9 (SD 1.77) g/dl, 31.7 (SD 5.31)% and 32.6 (SD 3.24) pg, respectively (P=0.023, P=0.049 and P=0.019).Conclusions : RET He were significantly higher after administration of intravenous iron supplement in iron deficient anemia in CKD patients with regular hemodialysis. These changes were also found in hemoglobin and hematokrit.Key words : anemia; chronic kidney disease; iron deficiency; reticulocyte hemoglobin equivalent